Entrepreneurial Empowerment in Hadith Perspective: A Study of Hadith Takhrij and Syarah - Azkiah, Nabila (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about entrepreneurial empowerment. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material method is about entrepreneurial empowerment in Abu Daud's narration No. 1471. The results and discussion of this study indicate that the status of the hadith is of sahih quality that meets the qualifications of maqbul. This study concludes that the Hadith narrated by Abu Daud No.1471 is relevant to be used as motivation, creativity, innovation, and entrepreneurial empowerment.